2022
DOI: 10.1039/d2tb00853j
|View full text |Cite
|
Sign up to set email alerts
|

Protein–inorganic hybrid porous scaffolds for bone tissue engineering

Abstract: Porous scaffolds hold promise in the treatment of bone defects for bone tissue engineering due to their interconnected porous structure and suitable mechanical properties. Herein, Laponite (LAP), which is able...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…The above results are consistent with the literature reports, that is, the incorporation of LAP into various polymer matrices stimulates osteogenic differentiation even in the absence of any osteoinductive factors [ 31 , 38 , 43 , 44 , 45 ]. For example, Xavier et al reported that after the addition of LAP, the ALP activity and calcium deposition of preosteoblast cells were significantly increased [ 44 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The above results are consistent with the literature reports, that is, the incorporation of LAP into various polymer matrices stimulates osteogenic differentiation even in the absence of any osteoinductive factors [ 31 , 38 , 43 , 44 , 45 ]. For example, Xavier et al reported that after the addition of LAP, the ALP activity and calcium deposition of preosteoblast cells were significantly increased [ 44 ].…”
Section: Resultssupporting
confidence: 93%
“…Similarly, Miao et al also found that the protein expressions of Runx2 and Col1 were significantly higher with the addition of LAP [ 38 ]. Recently, a novel RSF/LAP 3D porous scaffold with good biocompatibility and osteogenesis capacity was successfully developed in this laboratory [ 43 ]. The ALP activity and osteogenic-related gene and protein expression levels (BMP-2, Runx2, and OPN) also increased gradually with the LAP content.…”
Section: Resultsmentioning
confidence: 99%
“…The edges of newly formed bones ( Figure 10 c,f,i) displayed similar morphologies. The magnitude of the newly extended and formed bone was thought to be medium compared with other relevant studies [ 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 93%
“…Some novel approaches have been developed to create three-dimensional scaffolds based on biomaterials. Such scaffolds have advantages for tissue engineering, such as promoting cell adhesion, proliferation, migration, and differentiation [ 124 ]. Many natural and synthetic polymers produce scaffolds in skin tissue engineering [ 125 , 126 , 127 ].…”
Section: Biodegradable and Nondegradable Polymers For Wound Healingmentioning
confidence: 99%